PREDIKSI JUMLAH PENUMPANG ARMADA BUS PT. RAJA PERDANA INTI (RAPI) DENGAN SIMULASI MONTE CARLO - Wenny Marta Dolok Saribu; Riri Syafitri Lubis; Hendra Cipta (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
Prediction is an attempt to predict or predict something that will happen in the future by utilizing various relevant information at previous times through a scientific method. With the simulation system for predicting the number of passengers, it is hoped that it can predict the number of incoming passengers every day which will assist the company in determining the departure schedule for the PT. Raja Perdana Inti (RAPI). Monte Carlo can be used to find mathematical solutions consisting of many variables that are difficult to solve. The Monte Carlo simulation also applies a prediction simulation application as well as tests the level of accuracy and efficiency generated using this simulation. Based on the research, the prediction of the number of passengers in the bus fleet of PT. Raja Perdana Inti (RAPI) is 18719 people.